Seawater Acidification Reduced the Resistance of Crassostrea gigas to Vibrio splendidus Challenge: An Energy Metabolism Perspective - Cao, Ruiwen; Liu, Yongliang; Wang, Qing; Yang, Dinglong; Liu, Hui; Ran, Wen; Qu, Yi; Zhao, Jianmin (Frontiers in Physiology, 2018)
Negative physiological impacts induced by exposure to acidified seawater might sensitize marine organisms to future environmental stressors, such as disease outbreak. The goal of this study was to evaluate if ocean acidification could reduce the resistance capability of the Pacific oyster (Crassostrea gigas) to Vibrio splendidus challenge from an energy metabolism perspective. In this study, the Pacific oyster was exposed to ocean acidification (pH 7.6) for 28 days and then challenged by V. splendidus for another 72 h. Antioxidative responses, lipid peroxidation, metabolic (energy sensors, aerobic metabolism and anaerobic metabolism) gene expression, glycolytic enzyme activity and the content of energy reserves (glycogen and protein) were investigated to evaluate the environmental risk of pathogen infection under the condition of ocean acidification. Our results demonstrated that following the exposure to seawater acidification, oysters exhibited an energy modulation with slight inhibition of aerobic energy metabolism, stimulation of anaerobic metabolism and increased glycolytic enzyme activity. However, the energy modulation ability and antioxidative regulation of oysters exposed to seawater acidification may be overwhelmed by a subsequent pathogen challenge, resulting in increased oxidative damage, decreased aerobic metabolism, stimulated anaerobic metabolism and decreased energy reserves. Overall, although anaerobic metabolism was initiated to partially compensate for inhibited aerobic energy metabolism, increased oxidative damage combined with depleted energy reserves suggested that oysters were in an unsustainable bioenergetic state and were thereby incapable of supporting long-term population viability under conditions of seawater acidification and a pathogen challenge from V. splendidus.